5-[(Pyren-9-ylmethyl)amino]isophthalic acid with nitrogen containing heterocycles: stacking, N–H⋯π interactions and photoluminescence. Issue 39 (20th September 2021) - Sendh, Jagajiban; Singh, Munendra Pal; Baruah, Jubaraj B.
Abstract : Synthons guided the types of N–H⋯π interactions and stacking to cause quenching of emissions. Abstract : Different synthons, π-stackings and intermolecular N–H⋯π interactions guided by partner molecules in the cocrystals of a pyrene-derived dicarboxylic acid were demonstrated. For such a purpose the self-assemblies of a 1 : 1 solvate of dimethylformamide and 1 : 1 cocrystals with 6-phenyl-1, 3, 5-triazine-2, 4-diamine (PTDA), 4, 6-dimethylpyrimidin-2-amine (DMPA) or caffeine as well as a 2 : 1 cocrystal with phenazine (Phen) of 5-[(pyren-9-ylmethyl)amino]isophthalic acid (H2 L) were studied. The π-stackings among the pyrene rings in these self-assemblies were compared. Different synthons and stacking patterns in these assemblies were also evaluated. The DMF solvate as well as the PTDA cocrystal of H2 L had parallel π-stacks of pyrene rings, each of which were organised in a head-to-tail manner (where the head was the substituted end of pyrene and the tail was the opposite end of this). Both the assemblies had intermolecular N–H⋯π interactions. Phenazine was eclipsed between two isophthalic acid units in the phenazine cocrystal. It had η 3 -N–H⋯π intramolecular interactions. The assembly of the cocrystal with DMPA had pairs of stacked pyrene units organised in a parallel manner. These units were held together by intermolecular η 2 -N–H⋯π interactions. The cocrystal of caffeine with H2 L was obtained as a trihydrate. In this cocrystal the caffeine molecule was sandwiched between the π-stack of the two pyrene rings located on the top and the bottom side of the caffeine molecule. Self-assembly of a 1 : 1 salt, namely a mono-protonated 4, 4′-bipyridinium cation with [HL] −, was also analysed. The 4, 4′-bipyridinium salt of the HL anion had the pyrene rings assembled as pairs and were arranged in a head-to-tail arrangement. It lacked intermolecular N–H⋯π interactions. It had unusual pyridine–pyridine R22(6) synthons formed by C–H⋯N hydrogen bonds. Among the cocrystals the caffeine cocrystal was weakly fluorescent with a photoluminescence quantum yield (PLQY) 0.036, whereas the solid sample of the solvate and the other cocrystals as well as the salt of H2 L showed negligible emission.